Q: What is positive 6 minus negative 2?

Write your answer...

Submit

Related questions

When you multiply a negative number by a positive number then the product is always negative. When you multiply a positive number by a negative number then the product is always negative. ( - 2 ) ( + 3 ) = - 6 ( - 4 ) ( 1 ) = - 4 ( - 1 ) 2 = - 2 ( + 2 ) ( - 2 ) = - 4 ( 3 ) ( - 2 ) = - 6 4 ( - 2 ) = - 8

(+2) - (-6) = +8

if a positive number minus a negative number, the minus turns to a plus sign. so its positive Ex. 2- -4= 2+4=6

-6

0

It depends. (a) a positive minus a smaller positive is positive, (b) a positive minus a positive of the same size is zero, and (c) a positive minus a bigger positive is negative. For example, (a) 8 - 6 = 2 (b) 8 - 8 = 0 (c) 8 - 11 = -3

No. If x = -2, then y = -(2x) -(+6) = -2*(-2) - 6 = +4 - 6 = -2

positive 5 minus positive 11 = negative 6

It is: 10--6 = 16 because --6 is +6

Seven minus -6 is 13.

positive 6 minus positive 4 = (+6) - (+4)= +2

Goes towards positive.for instance, -7 minus -7 = 0or -10 minus -4 = -6OR -25 minus -30 = positive 5

A negative minus a negative turns the latter into a plus positive,for example -6 minus -3 would be :-6 ++ 3 = -3A minus negative always turns into a plus positive...To get more Specific:Suppose x and y are two POSITIVE numbers so that -x and -y are negative. Then a negative minus a negative = (-x) - (-y) = -x +yIf x > y the answer is negativeIf x = y the answer is zeroIf x < y the answer is positive

Six because 2 --4 = 6

-6

-6

3 minus -6 is 9.

You switch the numbers to 6 plus four, because it's the same thing. So, positive 6 minus negative 4 is 10.

minus a negative is plus a positive so something like -6 - -7=1 because its the same as-6 + +7

(-6) - (+1) = -7

-9 - 6 = -15

-5 - 6 = -11

A minus minus a minus will give a positive result. It will depend on the actual values. It will cause a positive movement, but still could result in a negative number. Consider these two examples. In both cases there is a positive movement but only the second results in an actual positive number:-6 - -2 = -4-2 - -6 = 4

-6Negative six(-3) - (+3) = -6

4.